IMPROVEMENT OF THE SYSTEM FOR HANDLING SAMPLES AND SPECIMENS OF GOODS IN CUSTOMS CONTROL (Multidisciplinary Journal of Science and Technology, 2026)
This article analysis the current state of the system for handling samples and specimens of goods within the customs authorities of the Republic of Uzbekistan, the regulatory and legal framework governing this process, international practices, and potential directions for system improvement. A comparison is made between China’s experience and the requirements of CM-145 (the Regulation “On the Procedure for Conducting Customs Expertise of Goods and Vehicles” dated February 21, 2022). Procedural uncertainties are identified, the need for digitalizing the process of sending samples and specimens to the Central Customs Laboratory is examined, and practical solutions and recommendations for implementing Chinese experience into national practice are presented.